Subversion of mRNA degradation pathways by EWSR1: FLI1 represents a therapeutic vulnerability in Ewing sarcoma - Galvan, Bartimée; Ongena, Loïc; Bruyr, Jonathan; Fettweis, Gregory; Lucarelli, Eva; Lavergne, Arnaud; Mariavelle, Emeline; O’Grady, Tina M.; Hassoun, Zahrat El Oula; Claes, Margaux; Dubois, Laurence; Lee, Kevin A. W.; et al. (Nature Communications, 2025)
Many cancers are defined by gene fusions that frequently encode oncogenic transcription factors (TFs), such as EWSR1::FLI1 in Ewing sarcoma (EwS). Here, we report that independently to its canonical roles in transcription, EWSR1::FLI1 also functions as an mRNA decay factor, reshaping mRNA stability in EwS. This function participates in EWSR1::FLI1 tumorigenicity and involves interactions of EWSR1::FLI1 with the CCR4-NOT deadenylation complex via its EWSR1-derived low-complexity domain and with the RNA-binding protein HuR/ELAVL1 via its FLI1-derived region. Strikingly, we find that EWSR1::FLI1-mediated mRNA decay antagonizes the normal mRNA protective function of HuR and renders EwS cells highly sensitive to HuR inhibition. Our findings uncover a post-transcriptional function of EWSR1::FLI1 and suggest that targeting mRNA stability mechanisms may offer therapeutic opportunities for EwS.
Gesehen am 28.11.2025